(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Several previous studies investigated the behavior of reinforced concrete blocks subjected to repeated loads, as well as the reinforcement of concrete corbels with various reinforcing materials such as carbon fiber tapes and steel fibers. In this current study, the variables are the type of concrete (normal and hybrid strength), reinforcement with steel plates, and load shedding (monotonic and repeated). Eight reinforced concrete cable samples were tested. During this investigation, three loading ratios were used based on the results of the selected samples: 25%, 50%, and 75% for each loading cycle. Vertical load testing was performed on four of the samples. The results were obtained with a shear extension to effective depth (a/d) ratio of 0.6. It can be seen that the load failure of samples tested under repeated loading systems is 7.74%, 16.21 %, 9.4 %, and 6.21 % lower than that of samples tested under monotonic loading systems, respectively. Because the amplitude of the first two cycles was less than the crushing load, 75 percent had the worst results in terms of maximum load reaching failure. The results showed that the first crack appeared in 25% of samples with monotonous loads and normal unreinforced concrete and in 18% of samples with repeated loads. The first loading rate of steel-reinforced concrete is 33.33% for monotonous and normal concrete samples and 22.35% for repeated load samples. New sloping cracks appeared and advanced along the shaft front when the load reached 75% of the failure load. These cracks widened and spread all the way to the upper shaft joint